1990
DOI: 10.1159/000119475
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Modulation of Growth Hormone-Releasing Hormone Effects on Growth Hormone Secretion in Dementia

Abstract: An impairment of cholinergic and somatostatinergic neurotransmission have been reported in dementia. Both acetylcholine and somatostatin are involved in the regulation of growth hormone (GH) secretion. The effects of GH-releasing hormone (GHRH) 1–44 on GH release have been studied before and after the pretreatment with pyridostigmine or pirenzepine in subjects with senile dementia of the Alzheimer type, multi-infarct dementia and mixed dementia. The data have been compared with those obtained in an age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(29 reference statements)
2
7
1
Order By: Relevance
“…Four out of 15 patients studied by us had early-onset disease and a clear GH response to all stimuli, but this pattern was also observed in older patients with late-onset disease. Moreover, in contrast to others [16,17], we did not find any delay in somatotroph responsiveness to GHRH alone or combined with PD or ARG in AD.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Four out of 15 patients studied by us had early-onset disease and a clear GH response to all stimuli, but this pattern was also observed in older patients with late-onset disease. Moreover, in contrast to others [16,17], we did not find any delay in somatotroph responsiveness to GHRH alone or combined with PD or ARG in AD.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies [15][16][17] showed no difference in the magnitude of the GHRHinduced GH release between AD patients and agematched controls.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, cholinergic agonists are able to increase both spontaneous and GHRH-induced GH secretion in AD patients [142,[152][153][154]156] without any difference with normal elderly [142,153], although both responses are reduced compared with normal young subjects [142]. These findings, therefore, confirmed the presence of neuroendocrine cholinergic derangement in the ageing brain but demonstrated that, at least at hypothalamic level, cholinergic pathways are not more impaired in AD than in normal elderly.…”
Section: Igf-imentioning
confidence: 54%
“…On the other hand, other studies focusing on the effects of other neuroactive drugs able to stimulate GH secretion, such as clonidine, pyridostigmine and apomorphine, generally confirmed that AD shows a GH response similar to that in normal elderly subjects [141,142,[152][153][154][155][156].…”
Section: Igf-imentioning
confidence: 77%